Investigating the effect of school‐wide positive behavioral interventions and supports on student learning and behavioral problems in elementary and middle schools. Issue 6 (2nd May 2018) - Ryoo, Ji Hoon; Hong, Saahoon; Bart, William M.; Shin, Jaehyun; Bradshaw, Catherine P.
Abstract: Many states have scaled up School‐Wide Positive Behavioral Interventions and Supports (SW‐PBIS) with the goal of improving student behavior and academic outcomes. Although the effects of SW‐PBIS on behavioral and discipline outcomes have been promising, the findings for academic achievement have been inconclusive and are often limited to cross‐sectional data. This paper examined the longitudinal effect of SW‐PBIS on student behavioral problems and academic achievement growth in elementary and middle schools using propensity score matching. We found no statistically significant longitudinal effects of SW‐PBIS on either student behavior problems or academic achievement among elementary and middle schools in this quasi‐experimental design, even though the positive direction of longitudinal changes would be identified. The result raised questions about the efficacy of SW‐PBIS using a statewide achievement test when scaled up to a state level. Additional research is needed to better understand the impact of SW‐PBIS using rigorous scale‐up designs.